Analisis Butir Soal Ujian Tengah Semester Bahasa Arab Kelas XII di SMA Al-Izzah IIBS Malang - Ramadhan, Rachmad; Firdaus, Fasich Nur (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
The focus of this research is to analyze the odd mid-semester exams for Arabic subjects for class X-IPS students at SMA Al-Izzah IIBS Malang in 2020-2021. The goal, so that Arabic language teachers are able to make good measuring tools in measuring student understanding, this study uses a qualitative approach through interviews, observations, documentation with data collection models obtained from student question sheets. then reduce the data, present the data, and draw conclusions to be presented as the final conclusion. To strengthen the data that has been found, the researcher applies triangulation as a technique for testing the validity of the data. The results showed: (1) by reducing the data, presenting the data, and drawing conclusions to be presented as the final conclusion. To strengthen the data that has been found, the researcher applies triangulation as a technique of testing the validity of the data. (2) on the written test, the type of test applied is a multiple choice test. In this test, there are 25 questions in which each question has 5 answer choices. In the first question the teacher asks questions about understanding. So that students not only know the rules of the Arabic language but also need to understand the meaning of the elements of the Arabic language being studied. In the second question the teacher gives questions that require students to analyze the questions to find answers. In this question, the teacher gives verses of the Qur'an as a sentence to be analyzed and determined through the multiple choices available. And in the third question the teacher gives questions that require students to understand the rules of Arabic. In this question, the teacher asks questions to compose Arabic sentences, but because this question is in the form of multiple choice, students only need to choose the answer asked by the teacher Abstrak fokus penelitian ini adalah menganalisis tengah semester ganjil mata pelajaran bahasa Arab siswa kelas X-IPS di Sma Al-Izzah IIBS Malang tahun 2020-2021. tujuannya, agar pengajar bahasa arab mampu membuat alat ukur yang baik dalam mengukur pemahaman siswa, penelitian ini menggunakan pendekatan melalui wawancara, observasi, dokumentasi dengan model penumpulan data yang didapatkan dari lembar soal siswa. kemudian mereduksi data-data, menyajikan data, dan menarik kesimpulan untuk disajikan sebagai kesimpulan akhir. Untuk memperkuat data yang telah ditemukan, peneliti menerapkan triangulasi sebagai Teknik pengujian keabsahan data. Hasil penelitian menunjukkan : (1) dengan mereduksi data-data, menyajikan data, dan menarik kesimpulan untuk disajikan sebagai kesimpulan akhir. Untuk memperkuat data yang telah ditemukan, peneliti menerapkan triangulasi sebagai Teknik pengujian keabsahan data (2) pada tes tulis, jenis tes yang diterapkan merupakan bentuk tes pilihan ganda. Pada tes tersebut butir soal terdiri dari 25 butir soal yang mana setiap soal memiliki 5 pilihan jawaban. Pada soal pertama guru memberikan pertanyaan tentang pengertian. Sehingga siswa tidak hanya mengetahui ilmu-kaidah bahasa Arab tetapi juga memahami pengertian dari unsur-unsur Bahasa Arab yang dipelajari. Pada pertanyaan kedua guru memberikan pertanyaan yang mengharuskan siswa untuk menganalisis soal untuk mencari jawaban. Disoal tersebut guru ayat al-Qu'an sebagai kalimat untuk dianalisis dan ditentukan melalui pilihan ganda yang tersedia. Dan pada soal ketiga guru memberikan soal yang mengharuskan siswa memahami kaidah-kaidah Bahasa Arab.